1988
DOI: 10.1083/jcb.107.4.1397
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine receptors and concanavalin A-binding sites on cultured Xenopus muscle cells: electrophoresis, diffusion, and aggregation [corrected and republished article originally printed in J Cell Biol 1988 May;106(5):1723-34]

Abstract: Using digitally analyzed fluorescence videomicroscopy, we have examined the behavior of acetylcholine receptors and concanavalin A binding sites in response to externally applied electric fields. The distributions of these molecules on cultured Xenopus myoballs were used to test a simple model which assumes that electrophoresis and diffusion are the only important processes involved. The model describes the distribution of concanavalin A sites quite well over a fourfold range of electric field strengths; the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 46 publications
9
60
1
Order By: Relevance
“…Using a model system-cultured Xenopus muscle cells exposed to electric fields-we have shown that AChRs, concentrated at the cathode-facing cell pole, continue to aggregate there after the field is terminated (Stollberg and Fraser, 1988). These observations are consistent with the possibility that the field-induced increase in receptor concentration triggers the aggregation event.…”
supporting
confidence: 75%
“…Using a model system-cultured Xenopus muscle cells exposed to electric fields-we have shown that AChRs, concentrated at the cathode-facing cell pole, continue to aggregate there after the field is terminated (Stollberg and Fraser, 1988). These observations are consistent with the possibility that the field-induced increase in receptor concentration triggers the aggregation event.…”
supporting
confidence: 75%
“…Beginning at the receptor level, a physiological EF physically moves charged receptor molecules exposed on the outer surface of the lipid bilayer and creates receptor asymmetry between cathodal-and anodal-facing membranes (89,163). An applied EF induces receptor asymmetries for the polysaccharide-binding plant lectins such as concanavalin A (conA) and for the neurotransmitter ACh on Xenopus myoblasts and on neurons (156,162,193). The epidermal growth factor (EGF) receptors on corneal epithelial cells (219) and on fibroblasts (73) also are redistributed by a physiological EF (Fig.…”
Section: Neuronal Growth Cone Turning and Induced Receptor Asymmetrymentioning
confidence: 99%
“…An important phenomenon induced by the application of direct current is electrolysis, that can alter acidbase balance, generating alkalosis or acidosis, which markedly alters cellular function. Changes in intracellular Ca2+ concentration have also been associated with direct current stimulation [46][47][48][49] . These results demonstrate that although tDCS promotes direct effects on the intrinsic electrical properties and parameters of neurotransmission, it also alters the cellular microenvironment and the molecules that compose it.…”
Section: Neurophysiological Backgroundmentioning
confidence: 99%
“…Although the effects of direct current stimulation directly influence the electrical properties of the membrane, alterations in the neuronal microenvironment may also justify the changes induced in its behavior [46][47][48][49][50] . In fact, migration and conformational change of proteins, alteration in tissue pH and incorporation of cholinergic receptors are some of the biological effects promoted by the application of exogenous continuous currents 25 .…”
Section: Neurophysiological Backgroundmentioning
confidence: 99%